The political system of the European Union - Hix, Simon; Høyland, Bjørn Kåre (Basingstoke Palgrave Macmillan, 2011)
The EU is presented in this textbook as an emerging political system, in which the government, policies and the politics of the system are inextricably linked
Introduction : explaining the EU political system -- Government. Executive politics ; Legislative politics ; Judicial politics -- Politics. Public opinion ; Democracy, parties, and elections ; Interest representation -- Policies. Regulation of the single market ; Expenditure policies ; Economic and monetary union ; Interior policies ; Foreign policies ; Conclusion : rethinking the European Union
Previous ed.: published by Simon Hix. 2005
Keywords: European Union; Political planning -- European Union countries; European Union countries -- Politics and government